Analisis Perubahan Kemiskinan Sektoral Indonesia Berdasarkan Sektor Kegiatan Ekonomi, Periode Kebijakan 2004 – 2017 - Ginanjar Syamsuar; Ono Tarsono (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2019)
Using Susenas data for 2004, 2009, 2014, and 2017, this study aims to calculate the size of aggregate and sectoral poverty during the development policy period of the three Indonesian administrations, 2004-2017, as well as identify which sectors contributed to changes in aggregate poverty. in Indonesia. The analysis used is a sectoral poverty decomposition analysis. The results of the analysis showed that in the three policy periods there was a decrease in aggregate poverty (P0), while the depth of poverty (P1) and poverty severity (P2) decreased only during the RPJMN-I and II policy periods, but during the RPJMN-III policy period they increased. During the RPJMN-I policy period poverty P0 decreased by 2.53 from 16.68 to 14.15, P1 decreased by 0.57 from 3.06 to 2.49, and P2 decreased 0.23 from 0.90 to 0.67, during the RPJMN-II policy period poverty P0 decreased 2.9 from 14.15 to 11.25, P1 decreased 0.74 from 2.49 to 1.75, and P2 decreased 0.23 from 0.67 to 0.44. The causes of the decline in aggregate poverty P0, P1, and P2 are dominant in the RPJMN-I and RPJMN-II due to intra-sectoral and inter-sectoral influences, in RPJMN-III the decline in aggregate poverty P0 is caused by intra-sectoral and inter-sectoral influences while the increase in P1 and P2 was caused by the interaction effect. Poverty alleviation during the policy period of RPJMN-I, RPJMN-II and RPJMN-III the reduction in the aggregate poverty level was significantly contributed by four main employment sectors, namely in RPJMN-I by the informal agriculture sector, formal/informal trade, formal/informal transportation, and formal/informal construction, in RPJMN-II by formal agriculture, formal trade, formal/informal transportation, and informal finance, and in RPJMN-III by informal agriculture, formal trade, formal/informal transportation, and formal/informal finance.